Indonesia : Can Community Preschools Improve Poor Children’s Development? - World Bank (Washington, DC, 2017)
In Indonesia, researchers evaluated a project to expand access to early childhood services in the country’s poorest areas by giving communities grants for preschools and providing teacher training and facilitators to encourage use of services. The evaluation found that this project boosted enrollment and children’s development, especially for those from the most disadvantaged backgrounds. Now, with support from the strategic impact evaluation fund, the research team is going back to see whether the early childhood services created with the project’s support are still functioning and how they are sustaining themselves given that project support has ended. As the Government of Indonesia considers expanding compulsory education to include pre-primary school, the results can provide important evidence for how to do this.